Civic Engagement Sebagai Penguatan Modal Sosial Dalam Bayang-Bayang Overburdening Community: Studi Kasus Pengelolaan Sampah Oleh KSM Randu Makmur Kab. Banyumas - Allya Zareva Arnesty; Iwan Nurhadi (LPPM Institut Pendidikan Nusantara Global, 2026)
Zero waste to landfill waste management is an important approach to reducing dependence on landfills (TPA), but its effectiveness is largely determined by community involvement and the strength of social capital within the community. This study analyzes the role of civic engagement in strengthening social capital, despite being under the shadow of overburdening communities, in the KSM Randu Makmur Community Self-Help Group as a waste manager at the Kedungrandu Integrated Waste Disposal Site (TPST), Banyumas Regency. This article aims to explore the practice of community engagement and its contribution to the effectiveness of waste management, using Robert Putnam's social capital theory. The research method uses a qualitative approach with a case study design, through data collection techniques of observation, in-depth interviews, and documentation. Data analysis was carried out using pattern matching and explanation building techniques. The results show that civic engagement in KSM Randu Makmur strengthens three dimensions of social capital: bonding through solidarity among workers, bridging through collaboration with the community and offtakers, and linking through vertical relationships with the Environmental Agency. This social capital supports operational effectiveness, increases public trust, and strengthens internal coordination. However, its effectiveness remains limited because waste sorting has not been implemented at the household level, so the burden of sorting falls entirely on the KSM Randu Makmur. KSM's civic engagement is not entirely born of ecological awareness, but also serves as a survival strategy amidst economic constraints, employment opportunities, and regulatory policies. The findings confirm that strengthening social capital through civic engagement can support the program's operational sustainability, but its effectiveness is partial and vulnerable because it occurs within the context of limited structural support and an unequal distribution of responsibilities.